2019
DOI: 10.1111/hepr.13338
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNA‐1246 as a possible biomarker for early tumor recurrence of hepatocellular carcinoma

Abstract: Aims Early tumor recurrence (ETR) after hepatic resection is a crucial predictor of poor prognosis in patients with hepatocellular carcinoma (HCC). The aim of this study was to identify clinically significant serum microRNAs (miRNAs) involved in the ETR of HCC. Methods We compared expression profiles of circulating miRNAs from serum samples between five HCC patients with ETR (recurrence within 12 months after hepatectomy) and five HCC patients without recurrence using microarray analysis of miRNA. The identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…miR-1246 was shown to have elevated serum levels in patients with ESCC in our previous study. Since then, other researchers have reported increased serum levels of this miR in other carcinomas ( 31 , 32 ). In a systematic review of gastrointestinal cancer, it was reported that the expression of miR-1246 in serum is more useful as a biomarker than that of miR-21, which is an oncomiR ( 12 ).…”
Section: Discussionmentioning
confidence: 89%
“…miR-1246 was shown to have elevated serum levels in patients with ESCC in our previous study. Since then, other researchers have reported increased serum levels of this miR in other carcinomas ( 31 , 32 ). In a systematic review of gastrointestinal cancer, it was reported that the expression of miR-1246 in serum is more useful as a biomarker than that of miR-21, which is an oncomiR ( 12 ).…”
Section: Discussionmentioning
confidence: 89%
“…In order to determine the effect of different combinations of reference genes in the normalization of a miRNA of interest, the RT-qPCR expression profile of three miRNAs related to HCC 34,35 , miR-1246, miR4454 and miR4443, was assessed at all time points. The differential expression of the three miRNAs resulted statistically significant only when normalized with miR-1280 compared to U6, which ranked second after the overall stability evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine the effect of different normalizers on the expression of circulating miRNAs, we profiled miR-1246, miR-4454 and miR-4443 during the follow-up of the patients. The three miRNAs were selected according to their possible relevance in HCC 34,35 . We compared the performances of the two highest-ranked normalizers, miR-1280 and U6.…”
Section: Reference Genes Stability During Patient's Follow-upmentioning
confidence: 99%
“…Several studies identified circulating miRNAs as therapy predictive markers [98] . Chuma et al [99] reported that serum miR-1246 predicted early tumor recurrence after hepatic resection. Cho et al [100] revealed that the levels of circulating miR-26a and miR-29a before treatment were prognostic markers for liver transplantation-free survival in hepatitis B virus-related HCC patients.…”
Section: Body Fluid Case Number Control/number Micrornas Regulationmentioning
confidence: 99%